Hide and Seek : Intelligence, Law Enforcement, and the Stalled War on Terrorist Finance - Cassara, John A., 1953- (Book collections on Project MUSE., 2006)
Examines the workings of the intelligence and law enforcement communities in both the pre- and post-9/11 world, focusing on their investigations into money laundering and terrorist finance.